Regenerative medicine techniques in cardiovascular disease: where is the horizon?. (May 2013) - Packer, Claire; Boddice, Beth; Simpson, Sue
Regenerative medicine techniques to restore cardiac and vascular function are being increasingly investigated as management options for cardiovascular disease. The authors set out to identify emerging regenerative techniques in cardiovascular disease and investigate their stage of development. The relevant networks in the field in the UK were contacted and online sources for cell therapy, tissue engineering, and other regenerative techniques and products were searched for online. A total of 49 Phase II, II/III and III trials of regenerative products or techniques were identified: 13 Phase III, eight Phase II/III and 28 Phase II trials. Twelve of the Phase III trials are for myocardial ischemia and involve an intracoronary infusion or intramyocardial injection of autologous bone marrow-derived stem cells. Most of those in Phase III trials are, however, associated either with an unproven delivery technique or cellular approach. The authors conclude that translation into clinical practice and diffusion into health systems is some way off.